New species and new distributional records of the hygropetric water scavenger beetle genus Oocyclus Sharp (Coleoptera: Hydrophilidae) from the Guiana Shield - Santana, Larissa; Short, Andrew Edward Z.; Benetti, Cesar João; Hamada, Neusa (Zootaxa, 2023)
The species of the water scavenger beetle genus Oocyclus Sharp are reviewed for the Guiana Shield region of South America. Seven species are recorded, including one here described as new: Oocyclus paraiso sp. n. from the Brazilian state of Pará. New records of previously described species are also reported for Brazil, French Guiana, Guyana, and Suriname. The aedeagus of O. coromoto Short & García is illustrated for the first time. As with all other known members of the genus, all Guiana Shield species are hygropetric habitat specialists. A key to the Oocyclus of the Guiana Shield is provided.